Too Late to Buy a Home? School Redistricting and the Timing and Extent of Capitalization - Xiaozhou Ding; Christopher Bollinger; Michael Clark; William H. Hoyt (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the past fifty years, a voluminous literature estimating the value of schools through capitalization in home prices has emerged. Prior research has identified capitalization using a variety of approaches including discontinuities caused by boundaries. Here, we use changes in school boundaries and the opening of a new school to identify this capitalization. Critical to properly estimating the effect of redistricting is to account for when information on the rezoning is available. We treat the information about the effects of zoning as occurring in three stages: announcement, approval of the zoning plan (map) and implementation. We find significant changes in values for homes redistricted to or from lower-performing schools and we find that this capitalization occurs well before implementation of the redistricting. As we show, failure to account for capitalization occurring before implementation will attenuate and even change the sign of capitalization.
Keywords: D10; I20; R30; 330; property values; hedonics; school quality; school district; difference-in-differences